ChemInform Abstract: Laser‐induced Magnetization Dynamics and Reversal in Ferrimagnetic Alloys. Issue 46 (18th November 2014) - Kirilyuk, Andrei; Kimel, Alexey V.; Rasing, Theo
Abstract Review: 165 refs.